2015
DOI: 10.2967/jnumed.115.166173
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Factors Determining the Enhanced Permeability and Retention Effect in Subcutaneous Xenografts

Abstract: Liposomal chemotherapy offers several advantages over conventional therapies, including high intratumoral drug delivery, reduced side effects, prolonged circulation time, and the possibility to dose higher. The efficient delivery of liposomal chemotherapeutics relies, however, on the enhanced permeability and retention (EPR) effect, which refers to the ability of macromolecules to extravasate leaky tumor vessels and accumulate in the tumor tissue. Using a panel of human xenograft tumors, we evaluated the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…It should be noted that the kidney filtration limit for nucleic acids was found to be 20–40 kDa 54 . Slowing excretion by the kidneys allows improved siRNA accumulation in the tumor because of the enhanced permeability and retention (EPR) effect, and in other organs through the endothelium vasculature depending on capillary pore size 55 . Our data showed that Ch-siRNA distribution in mouse internal organs does not depend on the presence or absence of a tumor (Figures 2 and 3) and apparently depends only on the conjugate nature, concentration of siRNA, and its circulation time in the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the kidney filtration limit for nucleic acids was found to be 20–40 kDa 54 . Slowing excretion by the kidneys allows improved siRNA accumulation in the tumor because of the enhanced permeability and retention (EPR) effect, and in other organs through the endothelium vasculature depending on capillary pore size 55 . Our data showed that Ch-siRNA distribution in mouse internal organs does not depend on the presence or absence of a tumor (Figures 2 and 3) and apparently depends only on the conjugate nature, concentration of siRNA, and its circulation time in the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, according to the literatures, the favorable permeability and good retention (EPR) effect are paramount for nanocarriers (including polymeric nanoparticles (Kawaguchi, 2000), liposomes (Zong et al, 2016), micelles (Sutton et al, 2007) and nanogels (Jung et al, 2008)) to accumulate in tumor tissues (Anitha et al, 2014;Bolkestein et al, 2016). Alternative formulations of free 5-Fu (such as microspheres, NPs, micelles and liposomes) (Udofot et al, 2015) could prolong retention time (Onishi & Machida, 2008;Huang et al, 2010;Li et al, 2014), reduce side effects (Wigmore et al, 2010;Noori et al, 2014) and improve bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…44–45, 61 Subcutaneous tumors also have abnormally high vascularity, artificially high leakiness and immunogenicity, and have decreased metastatic potential; such a model does not translate to clinical application. 12, 44 The use of iv injection verifies that our particles in fact target a model tumor, as opposed to relying on the less translationally relevant environment of a subcutaneous tumor or attributing particle targeting to diffusion after direct tumor injection. 34–35, 60 Orthotopic tumors using the cancer cell type of interest provide a more reliable model for testing clinical translation of new nanotechnologies.…”
Section: Resultsmentioning
confidence: 82%